Hubungan Komunikasi Terapeutik Perawat Dengan Tingkat Kecemasan Hospitalisasi Pada Anak Usia Prasekolah (3-6 Tahun) - vivin fitriya febrianti; Lilla Maria; Rahmawati Maulidia (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2020)
Pain and hospitalization create a crisis for the lives of children, because in hospitals children have to face a strange environment and meet caregivers they do not know. In this process the child can experience various events or experiences of hospitalization that are traumatic and full of anxiety. Professional nurses can play a role in reducing feelings of fear, anxiety and pain that are felt by children through service using therapeutic communication. The purpose of this study was to determine the relationship between therapeutic communication of nurses and anxiety levels of preschoolers age. The study design used correlational analysis with a cross-sectional approach. The population is parents with children who experienced hospitalization 67 respondents with a sampling technique using purposive sampling. The results of this study were nearly half the nurses had deficient therapeutic communication (44.8%) and almost half of the patients had severe anxiety levels (44.8%). The results of the Spearman test were obtained (r count) amounting to -0,904 and p value 0,000 so it can be concluded that there is a significant relationship between therapeutic communication nurses with anxiety levels of hospitalization in children. This study is expected so that nurses can improve therapeutic communication skills in providing nursing services through therapeutic communication training programs.